IJAR 2022
DOI: 10.36106/ijar/3114395
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting, a Review

Abstract: Water management is critical to any economy's growth and development, particularly in growing economies like India. However, due to excessive groundwater exploitation in the process of socioeconomic development and to meet the increased needs of the growing population, the resource is currently under stress. As a result, we should make use of this valuable resource while also conserving it. The basic goal of this study is to give a broad review of rainwater collecting systems and groundwater, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Likewise, the finding also indicates that establishing the rainwater harvesting system requires a series of years of study along with the total value of physical assets and the organizational membership of household members (Akther 2014;Beqaj, Marko, Çobani & Profka 2022;Gautam 2016). Furthermore, the study concludes that rainwater harvesting devices have been used to solve numerous waterrelated issues and can be used to supplement the public water supply (Jain, Chandrakar & Yadav 2022). Correspondingly The study found that one effective way to lessen water scarcity is to establish a small rainwater collection system that might collect enough water to meet family needs.…”
Section: Gutter Sizing and Installationmentioning
confidence: 89%
“…Likewise, the finding also indicates that establishing the rainwater harvesting system requires a series of years of study along with the total value of physical assets and the organizational membership of household members (Akther 2014;Beqaj, Marko, Çobani & Profka 2022;Gautam 2016). Furthermore, the study concludes that rainwater harvesting devices have been used to solve numerous waterrelated issues and can be used to supplement the public water supply (Jain, Chandrakar & Yadav 2022). Correspondingly The study found that one effective way to lessen water scarcity is to establish a small rainwater collection system that might collect enough water to meet family needs.…”
Section: Gutter Sizing and Installationmentioning
confidence: 89%